Choose the correct Options
0 of 25 Questions completed
Questions:
You have already completed the quiz before. Hence you can not start it again.
Quiz is loading…
You must sign in or sign up to start the quiz.
You must first complete the following:
0 of 25 Questions answered correctly
Your time:
Time has elapsed
You have reached 0 of 0 point(s), (0)
Earned Point(s): 0 of 0, (0)
0 Essay(s) Pending (Possible Point(s): 0)
Average score 

Your score 

Add 2 mn, 4 mn, 8 mn, 6 mn .
2 + (4) + 8 + (6) = 0
Add a + b – 1, b – a + 1, 1 – 26 .
Sum = (1 – 1)a + (1 + 1 – 2)b – 1 + 1 + 1 = 1
Add \(4x^{2}y, 3x^{2}y, 7xy^{2}, 7xy^{2}\) .
Simplify : p + (p – q) + q + (q – p)
p + p – q + q + q – p = p + q
Simplify : \(z^{2} + 11z^{2} – 5z – 11z^{2} + 5z\)
Subtract – xy from xy .
xy – (xy) = xy + xy = 2xy
Subtract \(y^{2}\) from \( – 5y^{2}\) .
What should be added to \(x^{2} + y^{2}\) to get \( x^{2} + y^{2} + 2xy\)?
What should be subtracted from \( x^{2} + y^{2} – 2xy\) to get \(x^{2} + y^{2}\)?
Find the value of the expression x + 2 for x = 2 .
(2) + 2 = 0
Find the value of the expression 4x – 3 for x = 1 .
4(1) – 3 = 1
Find the value of the expression \(100 – 10 x^{3}\) for \(x = 0\) .
100 – 10(0)3 = 100
Find the value of the expression 5n – 3 for n = 1 .
5(1) 3 = 8
Find the value of the expression \(x^{2} + 2x + 1 for x = – 1\).
Find the value of the expression a + b for a = 1, b = 2.
1 + 2 = 3
Find the value of the expression \(a^{2} – 2ab + b^{2}\) for a = 1, b = 1.
Find the value of the expression \(a^{2} – b^{2}\) for a = 2, b = 1.
Find the value of the expression \(a^{2} + b^{2}\)for a = 1, b = 0 .
Find the value of the expression \(a^{2} + ab + 1 \) for a = 0, b = 1.
Find the value of the expression 3x + 5 (x – 2) for x = 2 .
3(2)+ 5(2 – 2) = 6
Find the value of the expression \(z^{3} – 2(z – 10)\) for z = 10 .
Find the value of the expression – x + 2 for x = 2 .
[ (2) + 2 ] = 2 + 2 = 4
Find the value of the expression 3p + 7 for p = 2 .
3(2) + 7 = 1
Find the value of the expression \(a^{3} + b^{3} + c^{3} – 3abc\) for a = 2, b = 3, c = 4 .
If the value of the expression \(x^{2} – 5x + k\) for x = 0 is 5, then the value of k is